Measuring Library Service Excellence: Integrating Servqual with Accreditation Standards - Prastyabudi, Wahyu Andy; Latifah, Sephia Arda (LPPM Telkom University Surabaya, 2024)
The excellence of service provided by library serve as essential factors for maintaining student’s engagement and motivation in learning. However, the number of accredited libraries, indicating their quality, is relatively low. This paper aims to measure the service quality of a library owned by higher education institution in accordance with accreditation standards. Servqual (Service Quality) approach was employed with 20 distinct indicators derived from accreditation criteria. The respondents were students from a private university in Indonesia, accounting for 120. The method was followed by semi-structured interview for confirmatory analysis purpose. The findings reveal that 55% of the indicators rejected the null hypothesis, showing a negative gap between reality and expectations, which indicates a need for improvement. Quadrant-based mapping was utilised to identify the priority areas for improvement. Furthermore, list of recommendation based on accreditation component is provided, facilitating practical improvement steps for the library management.